Repeated Cocaine Exposure Attenuates the Desire to Actively Avoid: A Novel Active Avoidance Runway Task - Nguyen, David; Nesarajah, Yasika; Erb, Suzanne; Ito, Rutsuko (Frontiers in Behavioral Neuroscience, 2018)
Drug addiction is a disorder in which drug seeking persists despite aversive consequences. While it is well documented in animal models of drug sensitization that repeated drug exposure enhances positive incentive motivation for drug and natural reinforcers, its effect on negative incentive motivation, defined here as the motivation to avoid a cued aversive outcome, remains an open question. In the present study, we designed a novel active avoidance runway paradigm to assess the effects of repeated cocaine pre-exposure on the motivation to avoid an aversive outcome. Cocaine and saline pre-exposed rats were first trained to perform a conditioned active avoidance lever press response to prevent the occurrence of foot shock administrations. The rats were subsequently tested in a runway apparatus, wherein they were required to traverse the length of a straight alley maze to reach the lever and emit a conditioned active avoidance response. Run times were measured as an indication of negative incentive motivation. Cocaine pre-exposed rats demonstrated longer latencies to emit the conditioned active avoidance response, but showed no differences in latency to initiate runway behavior, nor in their acquisition of the active avoidance response compared to the saline pre-exposed controls. Subsequent testing in an elevated plus maze revealed no differences in the expression of anxiety in cocaine pre-exposed rats compared to saline pre-exposed controls. Our results indicate that prior repeated cocaine exposure attenuated cued negative incentive motivation, which suggests that drug addiction may be attributable to a decrease in motivation to avoid aversive consequences associated with drug use.